Stroke Recurrence and Antiplatelets in Posterior Versus Anterior Circulation Minor Stroke or Transient Ischemic Attack. Issue 4 (15th February 2023) - Liu, Huihui; Jing, Jing; Wang, Anxin; Xu, Qin; Meng, Xia; Li, Hao; Li, Zixiao; Wang, Yongjun
Abstract : Background: It is unclear whether infarct location affects stroke recurrence after index ischemic stroke. We aimed to compare the risk of stroke recurrence and the responses to dual antiplatelets with ticagrelor-aspirin versus clopidogrel-aspirin between patients with posterior circulation infarct (PCI) and those with anterior circulation infarct (ACI) after minor stroke or transient ischemic attack. Methods: Data were obtained from the double-blind CHANCE-2 trial (Ticagrelor or Clopidogrel With Aspirin in High-Risk Patients With Acute Nondisabling Cerebrovascular Events II), which was conducted across 202 centers in China from September 2019 to March 2021. Patients with positive diffusion-weighted imaging were included and classified into PCI and ACI groups according to the hyperintense lesions on diffusion-weighted imaging. The primary efficacy and safety outcomes were a new stroke and severe or moderate bleeding within 90 days, respectively. Results: A total of 4168 patients were included in this substudy, with 1427 PCI and 2741 ACI. During the 90-day follow-up, the risk of stroke recurrence in patients with PCI was similar to that with ACI (7.4% versus 8.3%; adjusted hazard ratio, 1.01 [95% CI, 0.79–1.29]; P =0.94). In comparison with clopidogrel-aspirin, ticagrelor-aspirin significantly reduced the risk of stroke recurrence in both the PCI (hazard ratio, 0.59 [95% CI, 0.40–0.89]; P =0.01) and ACI groups (hazard ratio, 0.65 [95% CI, 0.50–0.85]; P =0.002). There was no treatment-by-infarct location interaction ( P value for interaction, 0.92). The risk of severe or moderate bleeding was similar between PCI and ACI patients ( P =0.19). However, the risk of any bleeding increased on ticagrelor-aspirin than clopidogrel-aspirin treatment in PCI and ACI patients ( P =0.02 and 0.002, respectively). Conclusions: Our study demonstrated that stroke recurrence was similar between PCI and ACI in patients with minor stroke or transient ischemic attack. Additionally, ticagrelor-aspirin was superior to clopidogrel-aspirin in reducing the risk of stroke within 90 days in both PCI and ACI patients. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04078737.